Bahasa Inggris : Bahasa Inggris - Silitonga, Jeannette; Pangaribuan, Hisar; Waty, Lenita (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
This study aims to analyze the effect of an independent audit committee and corporate social responsibility disclosure on firm value in companies included in the Kompas 100 Index during 2023–2024. The research employs a quantitative methodology, leveraging secondary data from company reports and meeting the classical assumption tests. The results of the study indicate that the independent audit committee does not have a significant effect on firm value. Additionally, corporate social responsibility disclosure also does not show a significant effect on firm value. Simultaneous testing reveals that the independent audit committee and corporate social responsibility disclosure jointly still do not have a significant effect on firm value. These findings indicate that within the Kompas 100 Index during 2023–2024, oversight mechanisms through the audit committee and corporate social responsibility disclosure practices have not yet become primary factors directly reflected in firm value. Thus, firm value in this research sample is likely influenced more by other factors beyond the variables examined, or the impact of governance and corporate social responsibility disclosure may be indirect and only observable over a longer period of time.